Job satisfaction and organizational commitment of teachers in a public university in Peru - Quispe Flores, Ronald (2020)
The objective of this research was to evaluate the relationship between job satisfaction and organizational commitment of teachers from a public university in Peru, using the sequential explanatory design (QUAN → qual) of the mixed approach. The study population consisted of 256 teachers. The quantitative analysis of surveys obtained from 114 teachers chosen through intentional sampling was performed using descriptive statistics and multivariate logistic regression analysis. The qualitative analysis of interviews obtained from 8 teachers chosen on a proactive basis was carried out through ethnographic analysis. The results indicated that: satisfied teachers have 3.39 times greater the possibility of having an organizational commitment, compared to dissatisfied teachers ((OR) = 3.39, 95% CI: 1.22-9.44); 48.3% have dissatisfaction at work and 70.2% no have commitment to continuity; the main reasons were low salaries, lack of promotion, lack of appointment, lack of recognition and opportunities for growth. However, in recognition of the job opportunity they found at the university, 82.5% have an affective commitment and 57% have a normative commitment. In conclusion, there is a significant direct relationship between job satisfaction and organizational commitment; the neglect of the hygienic and motivational factors, cause job dissatisfaction and lack of commitment to continuity.